Potential of Single Transition Metal Atom Embedded C2N as Efficient Catalysts for N2O Reduction: Theoretical Investigation. Issue 3 (24th January 2023) - Liu, Xinmiao; Sheng, Li
Abstract: Converting the toxic air pollutant N2 O into less harmful gas has potential advantages. Herein, the feasibility of the N2 O reduction reaction over pristine C2 N and TM/C2 N (TM = V, Cr, Mn, Fe, Co, Ni, Cu, and Zn) monolayers are explored by density functional theory calculations with Grimme‐D3 correction. The results reveal that the existence of TM atoms indeed improves the adsorption performance of C2 N, where the TM atoms act as both electron acceptors and donors, favoring the activation of N2 O and CO molecules. Based on thermal stability, selectivity, and catalytic activity, TM/C2 N (TM = V and Mn) catalysts are screened from the above transition metal atoms. In particular, N2 O reduction is a thermodynamically and kinetically favorable pathway, which can take place with negligible energy barriers on V/C2 N and Mn/C2 N catalysts. The CO2 desorption on V/C2 N and Mn/C2 N catalysts is the rate‐limiting step with the desorption barrier of only 13.1 and 15.1 kcal mol −1, respectively. These results suggest that the screened TM/C2 N (TM = V and Mn) materials can be used as promising catalysts for the adsorption and reduction of environmentally unfriendly N2 O molecules. Abstract : Density functional theory is used to study the potential of TM/C2 N (TM = V, Cr, Mn, Fe, Co, Ni, Cu, and Zn) as efficient catalysts toward N2 O reduction. Based on the stability, selectivity, and catalytic activity, V/C2 N and Mn/C2 N are selected as promising candidate catalysts for the adsorption and reduction of environmentally unfriendly N2 O molecules.